The Impact of Docosahexaenoic Acid (DHA) Supplementation on Calcium Levels in Third Trimester Pregnant Women with Chronic Energy Deficiency (CED): A Correlational Study - Santosa, Rahajoe Imam; Siahaan, Salmon Charles; Gunawan, Erik Jaya; Pribadi, Florence; Bueya, Eirene Putri Febriani Pratama (UNUSA Press, 2024)
Background: Chronic Energy Deficiency (CED) during pregnancy represents a critical health challenge, especially in developing regions, where it significantly threatens maternal and fetal well-being. Docosahexaenoic Acid (DHA), an essential omega-3 fatty acid, plays a pivotal role in fetal neurodevelopment and maternal health. However, the impact of DHA supplementation on maternal calcium levels, particularly among pregnant women affected by CED, has not been extensively studied. This study evaluate the correlation between DHA supplementation and calcium levels in third-trimester pregnant women with CED, with the goal of improving outcomes for this vulnerable population. Method and Results: This research uses experimental cohort study design with a quantitative approach, using non-probability sampling techniques such as quota and purposive sampling, and involving a total of 24 participants. Statistical analysis revealed a significant increase in calcium levels following DHA supplementation, with a p-value of 0.007 (<0.05), indicating a notable impact of the intervention. The mean calcium levels post-treatment were higher than pre-treatment, demonstrating the efficacy of DHA supplementation in improving calcium levels. Further analysis showed no significant correlation between pre-supplementation calcium levels and Body Mass Index (BMI) (p = 0.622, > 0.05). However, a significant correlation was found between post-supplementation calcium levels and BMI (p = 0.002, < 0.05). These findings indicate a positive correlation between DHA supplementation and calcium levels in pregnant women with CED during the third trimester. However, further investigation is needed to fully understand the relationship between calcium levels and BMI. Conclusion: This study lays the groundwork for future research aimed at optimizing therapeutic interventions or supplementation strategies to improve the nutritional status of underweight pregnant women.